The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1155/2020/8861379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Novel Rhythmic Physical Activities on Fundamental Movement Skills in 3- to 5-Year-Old Children

Abstract: Based on traditional rhythmic physical activities (TRPA), we created novel rhythmic physical activities (NRPA). The purpose of this study was to verify the effectiveness of NRPA in improving children’s fundamental movement skills (FMS). 289 children (135 boys, 154 girls) from 3 to 5 years old were randomly divided into an experimental group and a control group. Tools of Test of Gross Motor Development-2, Tekscan instrument, and balance beam were to assess children’s FMS. Two-way repeated measures ANOVA was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…This meta-analysis was conducted using the R package meta version 7.0-0. Among the included studies, one study reported findings separately for males and females ( 20 ), while another study provided data for different age groups (4 and 5 years old) ( 21 ). To reduce the potential impact of bias from a single study on the overall effect, data from two separate groups within each study were combined to generate a composite score.…”
Section: Methodsmentioning
confidence: 99%
“…This meta-analysis was conducted using the R package meta version 7.0-0. Among the included studies, one study reported findings separately for males and females ( 20 ), while another study provided data for different age groups (4 and 5 years old) ( 21 ). To reduce the potential impact of bias from a single study on the overall effect, data from two separate groups within each study were combined to generate a composite score.…”
Section: Methodsmentioning
confidence: 99%
“…The BBT is a test of DB in which the subject walks on a 10 cm wide by 30 cm tall and 3 m long wooden balance beam ( Hu et al, 2020 ; Ke et al, 2021 ). This test has adequate validity and reliability for testing dynamic balance in children ( De Kegel et al, 2010 ; Latorre-Román et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sebaliknya apabila fundamental movement skill tidak terbina dengan optimal, maka akan berdampak terhadap keterampilan gerak yang rendah. Berdasarkan hasil studi yang dilakukan oleh Senturk et al, (2015) melaporkan bahwa penguasaan fundamental movement skill yang baik dapat memberikan manfaat yang besar bagi seseorang untuk melakukan berbagai aktivitas fisik dan menjadi modal utama bagi siswa dengan usia dini, remaja dan dewasa untuk sukses dalam melakukan keterampilan di suatu cabang olahraga (Hu et al, 2020). Selain itu, fundamental movement skill yang rendah akan menyebabkan siswa tidak aktif bergerak dan akan menyebabkan dampak negatif bagi siswa.…”
Section: Pendahuluanunclassified